ON THE METHOD OF SCHOOL COURSE OF PHYSICS TO STUDY THE MOVEMENT OF THE CHARGED PARTICLE IN ELECTRICAL AND MAGNETIC FIELDS - Mukashev, K.; Kusmanuly, K. (Recent Contributions to Physics, 2008)
The technique of the analysis of process of formation of movement of the charged particle is considered at its interaction with electric and magnetic the fields having various directions as among themselves, and in relation to a vector of speed of the charged particle.